2014
DOI: 10.1177/1099800413519494
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Immune Biomarkers as Predictors of MBSR(BC) Treatment Success in Off-Treatment Breast Cancer Patients

Abstract: Researchers focused on patient-centered medicine are increasingly trying to identify baseline factors that predict treatment success. Because the quantity and function of lymphocyte subsets change during stress, we hypothesized that these subsets would serve as stress markers and therefore predict which breast cancer patients would benefit most from mindfulness-based stress reduction (MBSR)-facilitated stress relief. The purpose of this study was to assess whether baseline biomarker levels predicted symptom im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 48 publications
2
38
0
1
Order By: Relevance
“…Reich et al [47] reported that the baseline biomarkers of study participants can influence the benefits they receive from MBSR training, and that adherence to an intervention protocol is also a key factor for ensuring that patients benefit from MBSR therapy [36,48].Although our meta-analysis contained no information regarding protocol adherence, our findings clearly showed that MBT was more effective for treating stress and depression than for treating anxiety. Therefore,…”
Section: Implications For Further Researchsupporting
confidence: 42%
“…Reich et al [47] reported that the baseline biomarkers of study participants can influence the benefits they receive from MBSR training, and that adherence to an intervention protocol is also a key factor for ensuring that patients benefit from MBSR therapy [36,48].Although our meta-analysis contained no information regarding protocol adherence, our findings clearly showed that MBT was more effective for treating stress and depression than for treating anxiety. Therefore,…”
Section: Implications For Further Researchsupporting
confidence: 42%
“…Eight m‐MBSR studies explicitly referred to a cancer‐specific version of MBSR known as mindfulness‐based cancer recovery (MBCR), and 3 stated delivering MBSR but provided no reference to the protocol and included insufficient intervention details to assess adherence to the original MBSR protocol. Five studies stated delivering the MBCT protocol: one reported delivering MBSR with components of MBCT, 2 reported using both MBSR and a second mindfulness protocol, and 2 did not provide any theoretical framework …”
Section: Resultsmentioning
confidence: 99%
“…Of the 28 studies reporting modifications to original MBSR or MBCT protocols, only one provided a full justification for why components were modified. A further 5 studies provided partial justification for the modifications to intervention components; however 19 studies mentioned but did not explain why modifications were necessary beyond participants being cancer patients . Mean quality score for justification of component changes was 1.27 (SD 0.8, range 0–3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Con distintos tipos de intervención, tales como grupos psico-educativos y de apoyo, la meditación e imaginación, el uso de técnicas de reducción de estrés, promoción de conductas de salud y mantenimiento y adherencia al tratamiento se observaron incrementos en la supervivencia (62)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72)(73). Los datos evidencian de los posibles beneficios de la intervención psicológica en distintos parámetros biológicos, en el incremento de la supervivencia y en la reducción en el riesgo de recaída.…”
Section: Efectos De La Intervención Psicológica En La Supervivenciaunclassified